Dental implant loaded with hydroxyapatite coating and preparation method thereof
By setting grooves on the neck of the dental implant and forming a hydroxyapatite coating, the problem of poor sealing effect of soft tissue around the dental implant and the type of macrophage polarization affecting the immune response is solved, and better inflammatory resistance and bone resorption reduction effects are achieved.
Patent Information
- Application Number
- CN202411968796.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
The soft tissue surrounding the dental implant has weak effect, which is prone to inflammation and bone resorption. The polarization type of macrophages affects the immune response, making it difficult to effectively prevent periimplant inflammation.
Grooves are set up at the neck of the dental implant, and a hydroxyapatite coating is formed on the surface of the groove. Grooves are opened by femtosecond laser technology, and treated with dopamine solution and simulated body fluids to promote collagen fiber growth and M2 polarization of macrophages.
It improves the sealing effect of soft tissue around the implant, promotes the proliferation and adhesion gene expression of fibroblasts and macrophages, enhances resistance to inflammation, and reduces the risk of bone resorption.
Smart Images

Figure CN119733104A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of dental implants, and in particular to a dental implant loaded with a hydroxyapatite coating and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Edentulous and edentulous are common and frequently occurring diseases in oral clinics, and are more common in the elderly. Edentulous and edentulous can reduce chewing and digestive functions, and affect pronunciation, facial appearance, neuromuscular system, etc., reducing the patient's quality of life. For edentulous and edentulous, implant dentures have unique advantages in restoring oral function and improving aesthetics, and have gradually become the preferred solution for repairing missing teeth.
[0004] The soft tissue around the implant is an important biological barrier to resist inflammation, prevent peri-implantitis, and reduce bone resorption. The epithelial tissue around the implant is similar to the epithelial tissue of natural teeth, but there are no vertically arranged collagen fibers inserted into the cementum like natural teeth around the implant. Its collagen fibers are often parallel to or surround the implant surface, resulting in the connective tissue sealing effect around the implant being significantly weaker than that of natural teeth. In addition, the lack of blood supply to the tissue around the implant makes its connective tissue similar to scar tissue, and its resistance to plaque and mechanical stimulation is not as good as that of natural teeth, making it prone to peri-implantitis and gingival recession, and even marginal bone resorption. Therefore, the barrier function provided by the soft tissue around the implant is very important.
[0005] At the same time, after implantation, the host immune response is activated, and immune cells including chemotactic macrophages are attracted to the site of injury. Macrophages show phenotypic plasticity according to the topological structure of foreign substances, and can be polarized into pro-inflammatory M1 and anti-inflammatory M2 types. M2 polarized macrophages can further recruit repair cells such as fibroblasts and endothelial cells to the wound surface in vivo and in vitro, promote the synthesis of extracellular matrix (ECM) and vascularization of endothelial cells, and are beneficial to the reconstruction of connective tissue and the healing of wound tissue surface. Compared with periodontitis lesions, the number of macrophages in the soft tissue of peri-implantitis is more, and the number of M1 macrophages accounts for a larger proportion, while the number of M2 macrophages shows similar levels in both. This suggests that macrophages play a role in tissue pathology such as inflammatory infiltration around implants, and their number and polarization type affect the immune response around implants. Therefore, it is very important to regulate the polarization response of macrophages in the soft tissue around implants through implant surface modification for the prevention of peri-implantitis. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a dental implant loaded with a hydroxyapatite coating and a preparation method thereof.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a dental implant loaded with a hydroxyapatite coating, comprising a neck and a body, wherein the neck and the body are coaxially arranged and integrally formed, and a plurality of parallel grooves are provided on the outer surface of the neck, wherein the grooves are coaxially arranged with the neck; and a hydroxyapatite coating is provided on the surface of the groove.
[0009] In one or more embodiments, the groove width is 10-30 μm, the groove spacing is 10-30 μm, and the groove depth is 2-10 μm.
[0010] In one or more embodiments, the longitudinal section of the groove is trapezoidal or rectangular.
[0011] In one or more embodiments, an external thread structure is provided on the outer surface of the body; the external thread structure is used for screwing and fixing with the jawbone.
[0012] In one or more embodiments, an end of the body away from the neck is an inverted cone structure.
[0013] In one or more embodiments, the thickness of the hydroxyapatite coating is 30 to 120 nm.
[0014] The second aspect of the present invention provides a method for preparing the dental implant loaded with hydroxyapatite coating according to the first aspect, comprising:
[0015] preparing a body of a one-piece dental implant and a neck without a groove;
[0016] Using femtosecond laser technology to create a groove in the neck;
[0017] The neck is immersed in a dopamine solution, and then immersed in a simulated body fluid, and after being taken out, cleaned, and dried, a dental implant loaded with a hydroxyapatite coating is obtained.
[0018] Dopamine can rapidly self-polymerize on the surface of inorganic and organic materials to form a tightly adherent polydopamine coating on the implant surface, which can serve as a secondary reaction platform. This is because the exposed hydroxyl groups on the polydopamine surface can act as nucleation sites to chelate calcium ions in the solution. In addition, due to electrostatic adsorption, a large number of calcium ions and phosphate ions can combine and form hydroxyapatite crystals on the implant over time and with the increase of solution saturation. The hydroxyapatite coating grows rapidly by consuming calcium and phosphate ions in the surrounding solution.
[0019] In one or more embodiments, the material of the body and the neck is selected from one of medical grade pure titanium, titanium alloy, pure tantalum or tantalum alloy.
[0020] In one or more embodiments, the method for preparing the body of the integrally formed dental implant and the neck without the groove is to cut the titanium column in one piece.
[0021] In one or more embodiments, the concentration of the dopamine solution is 1.5 to 3 mg / mL, preferably 2 mg / mL; the soaking time is 16 to 24 hours, preferably 24 hours.
[0022] In one or more embodiments, the concentration of the simulated body fluid is 1.5 to 2 times, preferably 1.5 times, that of the standard simulated body fluid.
[0023] In one or more embodiments, the temperature of immersion in the simulated body fluid is 36-40° C., preferably 37° C., and the immersion time is 110-130 h, preferably 120 h.
[0024] The beneficial effects of the present invention are:
[0025] The grooves provided on the neck of the dental implant of the present invention can guide the collagen fibers to grow perpendicular to the surface of the dental implant, thereby better forming the edge sealing effect of the soft tissue around the implant; at the same time, the grooves can also promote the proliferation and adhesion gene expression of fibroblasts, and the grooves combined with the micro-nano structure of hydroxyapatite can promote the proliferation of macrophages and fibroblasts, promote the polarization of macrophages to M2, secrete anti-inflammatory cytokines, and promote the migration of fibroblasts and the expression of adhesion genes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0027] Figure 1 Schematic diagram of the structure of a dental implant loaded with a hydroxyapatite coating; wherein 1-neck, 2-body, groove 3 and 4-external thread structure;
[0028] Figure 2 To detect the proliferation of fibroblasts on titanium sheets with grooves of different sizes using CCK8 assay;
[0029] Figure 3 To detect the expression of adhesion genes of fibroblasts on grooved titanium sheets of different sizes on the 7th day by PCR experiment;
[0030] Figure 4 To detect the proliferation of macrophages on different titanium sheet materials using CCK8 assay;
[0031] Figure 5 A and B in the figure both use PCR experiments to detect the expression of immune-related genes in macrophages by different titanium sheet materials;
[0032] Figure 6 To detect the secretion of inflammatory cytokines in macrophage supernatant by ELISA assay;
[0033] Figure 7 To detect the proliferation of fibroblasts under different titanium sheets and different culture conditions using CCK8 assay;
[0034] Figure 8 To detect the expression of fibroblast adhesion genes on different titanium sheets and under different culture conditions by PCR;
[0035] Fig. 9 To detect the migration of fibroblasts in different conditioned media using Transwell;
[0036] Fig.10 This is the result of the hard tissue cut slices in Example 4, stained with toluidine blue. DETAILED DESCRIPTION
[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0039] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0040] Example 1
[0041] Figure 1 Schematic diagram of the structure of a dental implant loaded with hydroxyapatite coating, reference Figure 1 A dental implant loaded with a hydroxyapatite coating comprises a neck 1 and a body 2, the neck 1 and the body 2 are coaxially arranged and integrally formed, a plurality of parallel grooves 3 are provided on the outer surface of the neck 1, the groove 3 is coaxially arranged with the neck 1; a hydroxyapatite coating is provided on the surface of the groove 1.
[0042] The groove 3 has a width of 10 to 30 μm, a groove pitch of 10 to 30 μm, and a groove depth of 2 to 10 μm. The longitudinal section of the groove 1 is a trapezoid or a rectangle.
[0043] In order to be tightly fixed with the jawbone, the outer surface of the body 2 is provided with an external thread structure 4; the external thread structure 4 is used for screwing and fixing with the jawbone. At the same time, in order to facilitate implantation in the jawbone, the end of the body 2 away from the neck is an inverted cone structure.
[0044] The thickness of the hydroxyapatite coating is 30 to 120 nm.
[0045] Example 2
[0046] 2.1 Using femtosecond laser technology, evenly spaced grooves were processed on the surface of a smooth titanium sheet: 10 μm in width, 10 μm in interval, and 3.5 μm in depth, named T10.
[0047] Using femtosecond laser technology, evenly spaced grooves were machined on the surface of a smooth titanium sheet: 15 μm in width, 15 μm in interval, and 3.5 μm in depth, named T15;
[0048] Using femtosecond laser technology, evenly spaced grooves were machined on the surface of a smooth titanium sheet: 30 μm in width, 30 μm in interval, and 3.5 μm in depth, named T30;
[0049] The diameter of the titanium sheet in T10, T15 and T30 is the same, which is 19.5mm, and grooves are processed on the entire titanium sheet.
[0050] T10, T15 and T30 were immersed in a dopamine hydrochloride solution (10 mM Tris buffer, pH 8.5, dopamine hydrochloride concentration of 2 mg / mL) overnight to fix polydopamine on the substrate surface; the obtained titanium sheet was rinsed with ultrapure water to remove excess dopamine and then dried.
[0051] In the simulated body fluid (1.5×SBF), the concentration is 1.5 times that of standard SBF. After immersion at 37°C for 5 days, the substrate was rinsed with double distilled water and dried.
[0052] 2.2 CCK8 assay was used to detect the proliferation of fibroblasts on titanium sheets with grooves of different sizes. The results are shown in Figure 2 As shown, from Figure 2 It can be seen that the smoother titanium sheet materials with grooves of different sizes showed obvious effects on promoting fibroblast proliferation at different time points on the 3rd, 5th and 7th days, especially in the T15 group.
[0053] 2.3 PCR experiments were used to detect the expression of adhesion genes on grooved titanium sheets of different sizes on the 7th day of fibroblast culture. The results are as follows Figure 3 As shown, the results showed that grooves of different sizes and smoother titanium sheet materials all showed the effect of promoting fibroblast adhesion, especially the T15 group had a more obvious effect on promoting adhesion gene expression.
[0054] Example 3
[0055] Group naming abbreviations: S is the smooth titanium sheet + complete medium group, MG is the grooved titanium sheet + complete medium group, MG-HA is the grooved combined hydroxyapatite titanium sheet + complete medium group, CM is the conditioned medium prepared with 1:1 macrophage culture supernatant and complete medium, S-CM is the smooth titanium sheet + conditioned medium group, MG-CM is the grooved titanium sheet + conditioned medium group, and MG-HA-CM is the grooved combined hydroxyapatite titanium sheet + conditioned medium group.
[0056] The complete culture medium is a high-glucose DMEM culture medium containing 10% fetal bovine serum + 1% double antibody.
[0057] 3.1 CCK8 assay was used to detect the proliferation of macrophages on different titanium sheet materials. The results are as follows Figure 4 As shown, the results showed that MG and MG-HA had significantly stronger effects on promoting macrophage proliferation than S, and the proliferation effect of MG-HA was more obvious.
[0058] 3.2 PCR experiments were used to detect the expression of immune-related genes in macrophages by different titanium sheet materials. The results are as follows Figure 5 As shown, the results showed that the grooved titanium sheet showed enhanced expression of both pro-inflammatory genes and anti-inflammatory genes compared with the smooth titanium sheet, and the grooved combined hydroxyapatite titanium sheet showed decreased expression of pro-inflammatory genes and enhanced expression of anti-inflammatory genes compared with the smooth titanium sheet.
[0059] 3.3 ELISA was used to detect the secretion of inflammatory cytokines in macrophage supernatant. The results are as follows Figure 6As shown, the results showed that the TNF-α secretion of the MG group was significantly increased compared with the smooth titanium sheet, and the IL-10 secretion of the MG-HA group was significantly increased compared with the smooth titanium sheet.
[0060] 3.4 CCK8 assay was used to detect the proliferation of fibroblasts under different titanium sheets and different culture conditions. The results are as follows Figure 7 As shown, the results showed that the groove group, the groove combined with hydroxyapatite group and the smoother titanium sheet under conditioned medium culture showed obvious effects on promoting fibroblast proliferation at different time points of 3, 5 and 7 days, especially the MG-HA-CM group.
[0061] 3.5 PCR was used to detect the expression of fibroblast adhesion genes under different titanium sheets and different culture conditions. The results are as follows Figure 8 As shown, the results showed that the groove group, the groove combined with hydroxyapatite group and the smoother titanium sheet cultured in conditioned medium all showed obvious effects on the expression of genes promoting fibroblast adhesion on the third day, especially the MG-HA-CM group.
[0062] 3.6 Transwell assay was used to detect the migration of fibroblasts in different conditioned medium (NC is conventional medium without macrophage supernatant). The results are as follows Fig. 9 As shown, the results showed that different conditioned medium promoted fibroblast migration more than conventional medium, among which conditioned medium of MG-HA had the best migration promoting effect, followed by MG, and the conditioned medium of smooth titanium sheet had a relatively weaker migration promoting effect.
[0063] Example 4
[0064] The body of the one-piece dental implant and the neck without a groove were prepared by integral cutting of titanium columns. A 0.7 mm groove was opened in the neck using femtosecond laser technology. The groove dimensions were: 15 μm in width, 15 μm in interval, and 10 μm in depth. A pure titanium dental implant with a groove structure was prepared, and a small amount of growth factor was added locally.
[0065] Bilateral mandibular premolars of beagles were extracted to construct a beagle tooth loss model. The above implants were implanted. The beagles were euthanized, and the entire mandible was sawed off and immersed in fixative. The mandible was cut into pieces with a single premolar as a unit using a hard tissue cutting and grinding system (EXAKT, Germany). The cut specimens were placed in running water for 24 hours to remove the internal formaldehyde, and then dehydrated and transparent according to the procedure. Then, a resin sample (Kulzer Technovit 7200VLC) was used for infiltration. The infiltrated specimens were placed in an embedding mold and polymerized under ultraviolet light. The polymer was cut in the mesiodistal direction and parallel to the long axis of the implant. The sections were micro-grinded and polished using a hard tissue cutting and grinding system to a uniform thickness of 30 to 40 μm. The sections were stained with toluidine blue for image observation.
[0066] The results are as follows Fig.10 As shown, the section results show that the soft tissue around the implant groove collar grows vertically on the implant surface.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A dental implant loaded with a hydroxyapatite coating, characterized in that: It comprises a neck and a body, wherein the neck and the body are coaxially arranged and integrally formed, a plurality of parallel grooves are provided on the outer surface of the neck, and the grooves are coaxially arranged with the neck; and a hydroxyapatite coating is provided on the surface of the grooves.
2. The dental implant according to claim 1, wherein: The groove width is 10-30 μm, the groove spacing is 10-30 μm, and the groove depth is 2-10 μm.
3. The dental implant according to claim 1, wherein: The longitudinal section of the groove is trapezoidal or rectangular.
4. The dental implant according to claim 1, wherein: The outer surface of the body is provided with an external thread structure; the external thread structure is used for screwing and fixing with the jawbone.
5. The dental implant according to claim 1, wherein: One end of the body away from the neck is an inverted cone structure.
6. The dental implant according to claim 1, wherein: The thickness of the hydroxyapatite coating is 30 to 120 nm.
7. The method for preparing a dental implant according to any one of claims 1 to 6, characterized in that: include: preparing a body of a one-piece dental implant and a neck without a groove; Using femtosecond laser technology to create a groove in the neck; The neck is immersed in a dopamine solution, and then immersed in a simulated body fluid, and after being taken out, cleaned, and dried, a dental implant loaded with a hydroxyapatite coating is obtained.
8. The preparation method according to claim 7, characterized in that: The material of the body and the neck is selected from one of medical grade pure titanium, titanium alloy, pure tantalum or tantalum alloy.
9. The preparation method according to claim 7, characterized in that The method for preparing the body of the one-piece dental implant and the neck without a groove is to cut the titanium column in one piece.
10. The preparation method according to claim 7, characterized in that: The concentration of the dopamine solution is 1.5 to 3 mg / mL, preferably 2 mg / mL; the soaking time is 16 to 24 hours, preferably 24 hours; Or, the concentration of the simulated body fluid is 1.5 to 2 times, preferably 1.5 times, that of the standard simulated body fluid; Alternatively, the temperature of immersion in the simulated body fluid is 36-40° C., preferably 37° C., and the immersion time is 110-130 h, preferably 120 h.